Oczekiwania uczestników zajęć dotyczące kompetencji zawodowych instruktorów fitness - Stanoch, Małgorzata; Szyszka, Dorota; Majewska, Małgorzata; Celka, Roman (Pedagogiczny wymiar kultury fizycznej i zdrowotnej w życiu współczesnego człowieka, 2016)
Purpose of the study: Establishing a model of professional competences of fitness instructors, running choreographic classes with music, based on the courses’ participants’ opinions depending on their training period. Research material and method: The respondents were clients of four fitness clubs in Poznań. The research material consisted of two groups: the participants with the training period in a fitness club shorter than 3 months (n = 75) and with the training period longer than half a year (n = 80). The research method was a diagnostic survey and a questionnaire was a research tool. Conclusions: The most essential fitness instructor’s trait, from the participants’ point of view, is motivating to physical effort, an ability to create a friendly atmosphere, warmth, a sense of humour, providing good energy. The training period slightly influences the practitioners’ expectations related to the instructors’ competences.